Update on Myopia Risk Factors and Microenvironmental Changes - Valeria Coviltir; Miruna Burcel; Alina Popa Cherecheanu; Catalina Ionescu; Dana Dascalescu; Vasile Potop; Marian Burcea (Journal of Ophthalmology)
The focus of this update is to emphasize the recent advances in the pathogenesis and various molecular key approaches associated with myopia in order to reveal new potential therapeutic targets. We review the current evidence for its complex genetics and evaluate the known or candidate genes and loci. In addition, we discuss recent investigations regarding the role of environmental factors. This paper also covers current research aimed at elucidating the signaling pathways involved in the pathogenesis of myopia.